Corrosion behaviour and mechanism of basalt fibres in acidic and alkaline environments. (September 2016) - Li, Zhuo; Xiao, Tongliang; Pan, Qingyan; Cheng, Junmei; Zhao, Shugao
Highlights: The concentration-dependent corrosion mechanism of basalt fibre was studied. Small ion depletion depth was gained for basalt fibre with high H2 SO4 concentration. The internal cracks primarily form with small ion depletion depth in H2 SO4 . Abstract: In this study, the corrosion behaviour and mechanism of basalt fibres immersed in H2 SO4 and NaOH solutions with a series of concentrations were investigated, and the effects of the H2 SO4 concentration on the stress corrosion were also studied. The corrosion is highly concentration-dependent, and the reaction rate directly determines the corrosion level. For H2 SO4 -corroded basalt fibre, the cracks between the outer layer and the inner core are primarily inclined to form when the ion depletion depth is small, whereas spiral and axial cracks are successively formed when the ion depletion depth is high.